Construction of integrated system for the treatment of Acid orange 7 dye from wastewater: Optimization and growth kinetic study - Kumar Sonwani R.; Pandey S.; Kumar Yadav S.; Shekhar Giri B.; Katiyar V.; Sharan Singh R.; Nath Rai B. (My University, 2025)
In this work, an effort has been made to develop an integrated system (ozonation followed by biodegradation) for the treatment of Acid orange 7 (AO 7) dye. The process parameters such as pH (3.0–11) and ozone dosage (5–25 mg/L) were optimized and obtained as 3.0 and 25 mg/L, respectively to treat the AO 7 by ozonation. Similarly, the process parameters, namely pH (5.0–9.0) and temperature (25–45 °C) were optimized and found to be 7.0 and 35 °C, respectively by biological treatment. Bacillus sp. was found to be the most effective bacteria to remove the AO 7. An integrated system obtained an overall 98.7% removal of AO 7 under optimum conditions. Andrews-Haldane model was best to predict the experimental data and the bio-kinetic constants; µmax: 0.1875 day−1; Ks: 49.53 mg/L; Ki: 133.32 mg/L were obtained. The developed integrated system can be a promising option for the treatment of azo dye containing-wastewaters. © 2021